Pengaruh Visual Storytelling Komik Asing pada Komik Indonesia Terbitan PT Elex Media Komputindo Tahun 2004-2008 - Yohan Alexander; Irfansyah Irfansyah (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2010)
In Indonesia, especially in the decade of 2000s, Japanese comic style was adapted and mimicked by Indonesian comic artists that tried to resurrect Indonesian comics industry that collapsed in the 1980s era. These comics were published by PT Elex Media Komputindo. There are possibilities that these comic artists indirectly also influenced by American and European comics imported and published in Indonesia at the end of 1980 decade. At the same time, this is an era where these comic artists have possibilities of great significant visual input before Japanese comics influenced them in the 1990s. So, the American and European comics could possibly had an impact for local comic artists.The research was done by defining visual storytelling theories before having an insight of the influence of foreign comics to the local comics. These theories would serve as a defining frame for American, European, Japanese comics to describe the influence on Indonesian comics. Some Indonesian comics published by PT Elex Media Komputindo at 2004-2008 span were used as case studies.From the research studies it had been discovered that American comics have the tendencies to visualize ideal form of human being in heroic acts. European comics have the tendencies to visualize everyday, ordinary characters doing adventures in extraordinary places. Japanese comics have the tendencies to visualize a journey story of a warrior in having his or her skills improved with in depth personal storytelling.Indonesian comics published by PT Elex Media Komputindo at 2004-2008 span had tendencies to be extensively influenced by Japanese comics. It could also be suggested by the restraining Japanese comics format proposed to the comic artists by the publisher. But on the other hand, Japanese comics were populer during 2000s decade, making the Japanese comics the main comic references for the comic artists. The research also discovered that American and European comics that were read also give some minor influences for the comic artist.